Cultivation of vetiver in saline tailings contaminated with arsenic under phosphorus doses - Guimarães, Lorena Abdalla de Oliveira Prata; Dias, Luiz Eduardo; Assis, Igor Rodrigues de; Cordeiro, Amanda Longhi (Revista Brasileira de Engenharia Agricola e Ambiental, 2016)
The processing of gold ores exploited in Paracatu, MG, generates tailings that are challenging for revegetation, mainly because of the high content of arsenic and salinity. Aiming at the revegetation of the area of disposal of these tailings, the objective of this study was to evaluate the effects of phosphorus doses on vetiver plants (Chrysopogon zizanioides) and on the planting substrate, which consisted of tailings from the processing of ore named B1, exploited in Paracatu, with water restriction. Vetiver was grown for four months in the substrate under doses of 0, 140, 280, 560 and 1280 mg kg–1 of P2O5. Increasing doses of phosphorus improved the chemical characteristics of the substrate. However, the highest dose (1280 mg kg–1 P2O5) resulted in higher toxicity of arsenic for the plants. Under the evaluated conditions, the dose of 560 mg kg–1 of P2O5 is the most suitable for the fertilization of vetiver and, therefore, also for the revegetation of the substrate. Vetiver survives under low availability of water in the tailings. © 2016 Departamento de Engenharia Agricola - UFCG/Cnpq. All rights reserved.
Cultivo de vetiver em um rejeito salino contaminado com arsênio sob doses de fósforo